The Hawaiian Quilt - Brunstetter, Wanda E.; Brunstetter, Jean (Uhrichsville, Ohio : Shiloh Run Press, an imprint of Barbour Publishing, Inc., 2016)
"Join Mandy Frey as she and three friends leave their Amish community in Indiana for the trip of a lifetime to Hawaii. But when Mandy and one of her friends miss the cruise ship after a port of call on Kauai, how will they adjust and get back home?"--Goodreads.com.
Keywords: Amish -- Fiction; Hawaiian quilts -- Fiction; Quilting -- Fiction; Ocean travel -- Fiction; Hawaii -- Fiction